Prvi i poslednji dani pontifikata pape Benedikta XVI: uporedna bogoslovska analiza - Stevanović, Nebojša (Sabornost, 2024)
The essential idea of the work is reflected in the comparative theological- historical analysis of the first and last days of the pontifical service of Pope Benedict XVI. In this context, the work is divided into several thematic units: after the introductory remarks, the direction of the work begins with the presentation of the basic biographical data of Ratzinger as a witness of great historical and theological changes, with a focus on the beginnings of theo- logical activity at the Second Vatican Council, and most directly in the days of the conclave and the election of the Pope. On those grounds, the further course of research is methodologically determined by the addresses, sermons and interviews of Benedict XVI, as the most authentic approach to the com- parative theological-historical analysis of his pontifical ministry, which mani- fests itself in two realities: the bishop of Rome and the Petrine ministry of the Pope. These two theological syntagms are discussed in the paper with a basic question: what is their place in the understanding of the theological thought of Benedict XVI in his first and last days of the pontificate. After presenting several statements of the mentioned phrases and trying to answer the essen- tial question of this part of the research, the analytical part is crowned with the question of the reasons and motives for the descent of Benedict XVI from the Peter’s Cathedra of Rome.